Social support in job performance as an antecedent of work intrusion on family conflict: empirical evidence - Ismail, Azman; Mohd Nor, Shifa; Yahya, Zulkifli; Ungku Zahar, Ungku Azly; Ismail, Yusof; Abu Samah , Ainon Jauhariah (University of Split, Croatia, 2013)
Potential impact of family conflict on an individual’s job performance cannot be underestimated as the latter is part of an employee’s life. An employee carries with him/her off job affairs when he/she goes to work as he/she brings home his work affairs although the extent varies and depends on a multitude of factors. The study was undertaken to examine the correlation between social support and work intrusion on family conflict. A survey method was used for data collection in a Malaysian navy base. Due to the administrative procedures of the authorities, the study used convenience sampling to administer the research instrument on male staff. The results of SmartPLS path model revealed two major findings: firstly, supervisor support is significantly correlated with work intrusion on family conflict. Secondly, coworker support is significantly correlated with work intrusion on family conflict. These findings suggests that high levels of supervisor and coworker’s support in performing one’s job have decreased the intrusion of work problems on employees’ family lives and upgraded their abilities to decrease family conflicts.